2015
DOI: 10.1109/mc.2015.166
|View full text |Cite
|
Sign up to set email alerts
|

Order Picking with Head-Up Displays

Abstract: Experiments suggest that using head-up displays like Google Glass to support parts picking for distribution results in fewer errors than current processes. Making Glass opaque instead of transparent further improves selection efficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0
6

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 7 publications
1
38
0
6
Order By: Relevance
“…It is an approach that is used for example in storage logistics. This problem is in detail described by Guo et al [5]. As one of the results of their research is the application of head-up displays which reduce errors in logistics processes and increases their efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…It is an approach that is used for example in storage logistics. This problem is in detail described by Guo et al [5]. As one of the results of their research is the application of head-up displays which reduce errors in logistics processes and increases their efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…In warehouse order picking, Guo et al (2015) carried out an experiment comparing the number of picking errors associated with various types of picking information systems. They found that systems in which the picking information is conveyed by a HUD or a cart-mounted display resulted in markedly fewer picking errors than did pick-by-light or a paper pick list.…”
Section: Previous Research Dealing With Quality In Kitting and Warehomentioning
confidence: 99%
“…Only in few cases some specific application scenarios of the industrial sector have been analyzed. For instance, Paelke [18] analyzed how workers can be supported using augmented reality and Guo et al [9] showed how picking processes in logistics can be simplified using head-up displays for employees. Even though there exists some research about the use of wearable computers in enterprises and the industrial sector, the adoption of wearable computers in enterprises has not been covered yet.…”
Section: Basics and Theoretical Background 21 Wearable Computersmentioning
confidence: 99%